Impact of photochemical processing of DOC on the bacterioplankton respiratory quotient in aquatic ecosystems - Lina Allesson; Lena Ström; Martin Berggren (Geophysical Research Letters)
Abstract Many studies assume a respiratory quotient (RQ = molar ratio of CO2 produced to O2 consumed) close to 1 when calculating bacterioplankton respiration. However, evidence suggests that RQ depends on the chemical composition of the respired substrate pool that may be altered by photochemical production of oxygen‐rich substrates, resulting in elevated RQs. Here we conducted a novel study of the impact of photochemical processing of dissolved organic carbon (DOC) on RQ. We monitored the bacterial RQ in bioassays of both ultraviolet light irradiated and nonirradiated humic lake water, using optic gas‐pressure sensors. In the experimentally irradiated samples the average RQ value was significantly higher (3.4–3.5 [±0.4 standard error (SE)]) than that in the dark controls (1.3 [±0.1 SE]). Our results show that the RQ is systematically higher than 1 when the bacterial metabolism in large part is based on photoproducts. By assuming an RQ of 1, bacterioplankton respiration in freshwater ecosystems may be greatly underestimated.